2001
DOI: 10.2166/wqrj.2001.008
|View full text |Cite
|
Sign up to set email alerts
|

Aeration Performance of Triangular Notch Weirs at Recirculating System

Abstract: An adequate supply of dissolved oxygen is essential for the survival of aquatic organisms. Hydraulic structures can increase dissolved oxygen levels by creating turbulent conditions, where small air bubbles are carried into the bulk of the flow. Plunging overfall jets from weirs at recirculating systems are a particular instance of this. This paper seeks triangular notch weirs having different weir angle (α) and how they affect the aeration performance. It is demonstrated that the aeration efficiency of a 90° … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Wilhelms et al [1], Chanson [2], Ervine [3], and Gulliver et al [4] reviewed studies about aeration efficiency of hydraulic structures. Recently, Baylar and Bagatur [5], Baylar and Bagatur [6,7], Baylar et al [8,9], Baylar [10], Baylar and Emiroglu [11] and Baylar and Bagatur [12] investigated sharp−crested weirs having different cross−sectional geometry and demonstrated that the air entrainment rate and the aeration efficiency of weirs changed depending on weir In this paper, artificial neural network (ANN) models and regression equations that were developed to determine the air entrainment rate and the aeration efficiency of the triangular sharp−crested weirs were compared to each others.…”
Section: Introductionmentioning
confidence: 98%
“…Wilhelms et al [1], Chanson [2], Ervine [3], and Gulliver et al [4] reviewed studies about aeration efficiency of hydraulic structures. Recently, Baylar and Bagatur [5], Baylar and Bagatur [6,7], Baylar et al [8,9], Baylar [10], Baylar and Emiroglu [11] and Baylar and Bagatur [12] investigated sharp−crested weirs having different cross−sectional geometry and demonstrated that the air entrainment rate and the aeration efficiency of weirs changed depending on weir In this paper, artificial neural network (ANN) models and regression equations that were developed to determine the air entrainment rate and the aeration efficiency of the triangular sharp−crested weirs were compared to each others.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Gameson [24], Avery and Novak [2], Tsang [38], Nakasone [35], Chanson [18], Tang et al [37], Labocha et al [30], Watson et al [39], Wormleaton and Soufiani [40], Wormleaton and Tsang [41], Baylar and Bagatur [5][6][7][8], Baylar et al [9,10,14,15,17], Baylar and Emiroglu [11], Baylar [3,4], Emiroglu and Baylar [20][21][22][23], Baylar and Ozkan [13], Ozkan et al [36] and Kaya [28] studied on air-demand ratio (ratio of volume flow rate of air to that of water) and aeration efficiency in weirs.…”
Section: Introductionmentioning
confidence: 99%
“…These studies are reviewed by Wilhelms et al (1992); Chanson (1995); Ervine (1998); Gulliver et al (1998). Baylar & Bagatur (2000, 2001a, b). Baylar et al (2001a, b) demonstrated that the aeration performance of weirs changed, depending on weir shapes.…”
Section: Introductionmentioning
confidence: 99%